ChemInform Abstract: Synthesis of 5‐Cyanopyrazolo[1, 5‐a]pyridine Derivatives via Tandem Reaction and Their Optical Properties. Issue 22 (15th May 2015) - Wang, Bin; Su, Fan; Jia, Jiong; Wu, Fan; Zhang, Shu‐Yao; Ge, Yan‐Qing; Wang, Jason; Wang, Jian‐Wu
Abstract: A novel tandem reaction of 5‐carbonylpyrazole derivatives with 4‐bromobut‐2‐enenitrile provides access to pyrazolopyridine derivatives displaying blue fluorescence.